A CROSS-SECTIONAL STUDY OF PATHOLOGICAL SCORING OF PHOSPHATASE AND TENSIN HOMOLOG (PTEN) IMMUNOHISTOCHEMISTRY IN ENDOMETRIAL CARCINOMA, ODISHA: DIAGNOSTIC, PROGNOSTIC AND THERAPEUTIC EFFICACY - Bidyut Prabha Satpathy,; Sonali Kar,; Sugatha Sahu, (Student's Journal of Health Research Africa, 2024)
Background Endometrial carcinoma (EC), the most common gynecologic cancer, is rising, especially in postmenopausal women. Identification of reliable prognostic indicators is essential for early diagnosis and patient management. EC is often linked to the tumor suppressor gene PTEN (Phosphatase and Tensin Homolog), suggesting it could be used as a diagnostic and prognostic marker. This study evaluated the expression of PTEN in endometrial tissues diagnosed with hyperplasia and carcinoma, and to correlate PTEN expression with the type and grade of EC. Methods Endometrial tissue samples from 66 patients were analyzed, including 30 cases of endometrioid endometrial carcinoma (EEC), 12 cases of proliferative endometrium (PE), 12 cases of endometrial hyperplasia (EH), and 12 cases of non-endometrioid uterine malignancies (NEUM). PTEN expression was assessed using immunohistochemistry on paraffin-embedded tissue sections, and statistical analysis was accomplished using SPSS version 20. Results The participants' ages ranged from 42 to 68 years, with a mean age of 55.4 years. PTEN expression was substantially lower in EEC in contrast to PE and EH (p = 0.0001). The mean PTEN scores were 235.83 ± 26.79 for PE, 94.17 ± 61.27 for EH, 31.67 ± 58.37 for EEC, and 61.67 ± 79.64 for NEUM. A significant correlation was found between reduced PTEN expression and higher tumor grade, increased myometrial invasion, and advanced tumor stage (p < 0.05). Conclusion PTEN expression is substantially reduced in EC, particularly in higher-grade tumors and those with extensive myometrial invasion. This study underscores the potential of PTEN as a prognostic marker in EC, which could be instrumental in guiding treatment strategies. Recommendations Further studies with higher sample numbers are recommended to validate PTEN as a routine diagnostic and prognostic marker in clinical practice. Additionally, exploring the role of PTEN in targeted therapies could provide new avenues for the treatment of EC.